The Impact of the Latest Health Data Privacy Regulations on Patient Information Access Policies in Healthcare Service Facilities - Antik Pujihastuti; Yuyun Manggandhi; Khofifah Rafika (Research and Evidence on Knowledge in Administration and Management — Medical Electronic Data and Information Systems, 2025)
This investigation scrutinizes the impact of Indonesia's Law No. 27 of 2022 (UU PDP) on patient information access policies in healthcare institutions. Employing a qualitative methodology based on secondary data content analysis of national statutes, ministerial regulations, and professional guidelines, the study assesses the legal and ethical ramifications for clinical data management. Key findings indicate a significant strengthening of patient rights, evidenced by mandatory explicit consent and the implementation of role-based access protocols, coupled with advanced security adoption in large hospitals. Conversely, regional facilities confront considerable challenges from limited infrastructure and inadequate human capital, leading to elevated data breach susceptibility. Persistent legal enforcement issues and ethical dilemmas necessitate continuous training and clear operational guidelines. The research emphasizes the critical need for integrated enforcement, technical modernization, and coordinated stakeholder action to ensure the secure and equitable handling of patient data, aligning with international standards. Future research should focus on scalable technological and ethical awareness solutions.